How to Translate Firm-Generated Content to Sales? Evidence from Online Healthcare Platforms - Qiao, Wanxin; Huang, Ni; Yan, Zhijun (Journal of Management Information Systems, 2024)
Firm-generated content (FGC) is increasingly popular in practice, yet the mechanisms underlying its effects on sales, particularly in specialized contexts such as online healthcare, remain underexplored. This study investigates the effects of FGC on sales, the mediating role of user-generated content (UGC) characteristics, and the moderation effects of contextual factors in online healthcare platforms. Grounded in the uses and gratifications theory, we hypothesize how FGC influences sales volume and explore the potential mediation roles of UGC length as well as affective, cognitive, and social content in UGC. A key empirical tension arises from understanding whether FGC directly and completely drives sales or whether its impact is partially mediated through UGC characteristics. We employ counterfactual estimators to assess the impact of FGC on sales. We then examine how UGC characteristics (affective, cognitive, and social), as mediators, help explain the main relationship. Next, we perform a series of moderation analyses and explore the contextual characteristics in translating FGC to sales. Our results show that FGC increases the volume of sales, partially through its influence on UGC pathways. Specifically, FGC increases the length of UGC, reduces affective UGC, and increases social UGC. The length of UGC serves as an important mediator between FGC and sales. Meanwhile, affective UGC and social UGC capture significant mediating effects on the relationship between FGC and sales, while cognitive UGC does not mediate the relationship between FGC and sales. Furthermore, we observe several moderating factors: the effects of FGC are stronger for medical institutions that are privately owned, located in smaller cities, and have fewer doctors. Our findings demonstrate that the impact of FGC is shaped not only by UGC characteristics but also by institutional factors such as ownership, location, and size. This work contributes to the literature on FGC by offering novel insights into the UGC-related mechanisms through which FGC influences sales in online healthcare platforms. It also provides practical implications on the role of digital content characteristics in consumer decision-making, especially in high-stakes situations such as healthcare.